The funeral culture of the indigenous communities of Mexico and the Mesoamerican riligious imagination - Barbosa Sánchez, Alma Patricia (2018)
In spite of the historical brunt of Western culture and catholic evangelization, the Mexican indigenous communities preserved, within their oral tradition and funerary culture, two basic premises of the Mesoamerican religious imaginary: the conception of life/death duality and the body/soul duality. Periodically, and on the fringes of Catholic liturgy, they perform sui géneris rituals, where they establish a communication and collaboration with the deceased. Oral testimonies explain the conception of the supernatural world, as well as the existence of the deceased, within the basic premises of the Mesoamerican religious imaginary.